2015
DOI: 10.1074/jbc.m114.607952
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the Small Conductance Calcium-activated Potassium Channels in Diabetic Mouse Atria

Abstract: Background: SK channels are implicated in atrial fibrillation (AF), and diabetes (DM) is a risk factor for AF. Results: Atrial SK2 and SK3 are significantly down-regulated from accelerated turnover in diabetic mice, resulting in action potential prolongation and arrhythmias. Conclusion: SK channel down-regulation may lead to arrhythmogenesis. Significance: SK channel down-regulation contributes to atrial electrophysiological dysfunction in DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 32 publications
(42 reference statements)
8
40
0
Order By: Relevance
“…These observations support the notion that ROS play an important causative role in chronic hypoxia-induced BK Ca channel repression and dysfunction in uterine arteries. Consistent with the present findings, oxidative stress was attributed to down-regulation of the BK Ca channel β1 subunit in arteries, as well as SK Ca and IK Ca channels in atria of diabetic rodents (Lu et al 2012;Zhao et al 2014;Yi et al 2015). Taken together, these studies provide evidence that the direct effect of chronic hypoxia regulates BK Ca channel function in uterine arteries of pregnant animals via increased oxidative stress, involving both post-translational modification and gene expression.…”
Section: Ros Include Oxygen Radicals Such As Superoxide (Osupporting
confidence: 91%
See 3 more Smart Citations
“…These observations support the notion that ROS play an important causative role in chronic hypoxia-induced BK Ca channel repression and dysfunction in uterine arteries. Consistent with the present findings, oxidative stress was attributed to down-regulation of the BK Ca channel β1 subunit in arteries, as well as SK Ca and IK Ca channels in atria of diabetic rodents (Lu et al 2012;Zhao et al 2014;Yi et al 2015). Taken together, these studies provide evidence that the direct effect of chronic hypoxia regulates BK Ca channel function in uterine arteries of pregnant animals via increased oxidative stress, involving both post-translational modification and gene expression.…”
Section: Ros Include Oxygen Radicals Such As Superoxide (Osupporting
confidence: 91%
“…Our recent studies demonstrated that long-term high-altitude hypoxia during gestation increased ROS production in ovine uterine arteries, in part due to increased expression and activity of Nox2 . It has been shown that ROS are implicated in down-regulating BK Ca channels, as well as small (SK Ca ) and intermediate (IK Ca ) conductance Ca 2+ -activated K + channels in the cardiovascular system (Lu et al 2012;Zhao et al 2014;Yi et al 2015). Herein, we present novel evidence that prolonged hypoxia has a direct effect in inhibiting the BK Ca channel activity in uterine arteries by increasing oxidative stress.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…[79] The SK current is downregulated in diabetic mouse atria and in human chronic atrial fibrillation (AF). [10,11] Inhibition of SK current is proarrhythmic in healthy atria but antiarrhythmic in atrial tachypacing-induced remodeled atria due to the associated increase in action potential duration. [1215] Although SK current is either very small or undetectable in normal ventricular myocytes paced at normal rates, [1618] it is important for ventricular repolarization in normal hearts with bradycardia and/or hypokalemia, as well as in ischemic and failing ventricles.…”
Section: Introductionmentioning
confidence: 99%